PERBANDINGAN INDEKS BARTHEL DENGAN SKALA TINGKAT DISABILITAS RAPPAPORT DALAM MENILAI KELUARAN FUNGSIONAL PADA PASIEN CEDERA KEPALA SEDANG DAN BERAT - Thomas*, Basuki A*,Sobaryati* (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION HEAD INJURY IS A MAJOR HEALTH PROBLEM SPECIALLY IN PRODUCTIVE AGES THE LARGE IMPACTOF THE PROBLEM ARE DISSABILITY PHYSICALLY EMOTIONALLY AND PSYCHOSOCIAL FUNCTIONAL OUTCOME MEASURESINPATIENT IS VERY IMPORTANT FOR REHABILITATION AND MONITORING PROGRAM MANY TOOLS DEVELOPED TOMEASURE THOSE DISSABILITY BARTHEL INDEX AND RAPPAPORT DISSABILITY SCALE IS ONE OF THEM